2021
DOI: 10.1111/1462-2920.15457
|View full text |Cite
|
Sign up to set email alerts
|

Plant holobiont interactions mediated by the type VI secretion system and the membrane vesicles: promising tools for a greener agriculture

Abstract: A deeper understanding of the complex relationship between plants and their microbiota is allowing researchers to appreciate a plethora of possibilities to improve crops using chemical-free alternatives based on beneficial microorganisms. An increase in crop yield from the promotion of plant growth or even simultaneous protection of the plants from the attack of phytopathogens can be achieved in the presence of different plant-associated microorganisms known as plant-growthpromoting rhizobacteria (PGPR) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The KT2440 strain studied in this work represents a well-established biological control agent [46]. Importantly, this strain is the model organism employed to study the role of the T6SS as a potent molecular weapon to control plant pathogens [5,11,66].…”
Section: Discussionmentioning
confidence: 99%
“…The KT2440 strain studied in this work represents a well-established biological control agent [46]. Importantly, this strain is the model organism employed to study the role of the T6SS as a potent molecular weapon to control plant pathogens [5,11,66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous, study revealed that this strain is able to help manage several plant diseases by producing antibiotics, competition with other pathogens for space and nutrients, and stimulation of host systemic resistance ( Riaz et al, 2022 ). This bacterial strain has a Type-VI Secretion System (T6SS) used to kill and eradicate plant pathogens and is vital in its bio-control portfolio ( Borrero de Acuña and Bernal, 2021 ). It was found promising against several destructive plant pathogens such as Fusarium oxysporum in tomato, Rhizoctonia solani in potato and Pectobacterium atrosepticum in potato, Sclerotinia sclerotiorum in lettuce and Ralstonia solanacearum in tomato ( Bernal Guzmán et al, 2017 ; Durán et al, 2021 ).…”
Section: Biological Controlmentioning
confidence: 99%
“…Pseudomonas putida, a Gram-negative bacterium, benefits crop plants by acting as a phosphate solubilizer and biocontrol agent (Sun et al, 2017;Takishita et al, 2021). The bacterium has a Type VI Secretion System (T6SS) to kill phytopathogens, which is important in its biocontrol portfolio (Borrero De Acuña and Bernal, 2021). It was found effective for a number of destructive plant pathogens like F. oxysporum in tomato, Rhizoctonia solani and Pectobacterium atrosepticum in potato and Sclerotinia sclerotiorum in lettuce (Bernal et al, 2017;Durán et al, 2021).…”
Section: Introductionmentioning
confidence: 99%